2016
DOI: 10.1088/1361-6463/50/2/024001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental models for Murray’s law

Abstract: Transport networks are ubiquitous in multicellular organisms and include leaf veins, fungal mycelia and blood vessels. While transport of materials and signals through the network plays a crucial role in maintaining the living system, the transport capacity of the network can best be understood in terms of hydrodynamics. We report here that plasmodium from the large, single-celled amoeboid Physarum is able to construct a hydrodynamically optimized vein-network when evacuating biomass from confined arenas of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 41 publications
6
35
0
Order By: Relevance
“…Evacuation networks were formed by allowing an excised sheet of protoplasm to exit an enclosed rectangular arena through a single channel in response to addition of a food source according to [1]. Time lapse images were obtained with transmitted light with an (x, y) pixel spacing of 6.2µm, at 1 h intervals and imported into a MATLAB GUI for all subsequent processing steps.…”
Section: A Establishment Of Evacuation Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Evacuation networks were formed by allowing an excised sheet of protoplasm to exit an enclosed rectangular arena through a single channel in response to addition of a food source according to [1]. Time lapse images were obtained with transmitted light with an (x, y) pixel spacing of 6.2µm, at 1 h intervals and imported into a MATLAB GUI for all subsequent processing steps.…”
Section: A Establishment Of Evacuation Networkmentioning
confidence: 99%
“…We have previously examined the scaling relationship between parent and daughter vessel radii at three-way junctions [1] to test whether Physarum networks obey Murray's law [38]. This predicts that the radius r 0 of a parent vessel is related to the radii of the daughter vessels r 1 and r 2 by the relationship:…”
Section: G Analysis Of Predicted Flowsmentioning
confidence: 99%
“…If the original binary image correctly covers the complete vein width, the Euclidean Distance Map (EDM, [25]) or the segmented areato-length ratio [4], can be used to estimate the width. Alternatively, the original intensity image can be interrogated directly using calibrated measurements of light transmission following the Lambert-Beer law [1], or using greyscale granulometry techniques [39].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that taking µ in an appropriate regime is crucial to reproducing these behaviours [7]. Based on the analysis in [32], we take µ = 1. 3 The time scales of actomyosin contraction and migration are determined by τ 1 and τ 2 .…”
Section: Actomyosin Contraction Experimental Studies Havementioning
confidence: 99%